Unlocking the Failure Mechanism of Solid State Lithium Metal Batteries - Liu, Jia; Yuan, Hong; Liu, He; Zhao, Chen‐Zi; Lu, Yang; Cheng, Xin‐Bing; Huang, Jia‐Qi; Zhang, Qiang (Advanced energy materials, 2022)
Solid‐state lithium metal batteries are regarded to be the ultimate choice for future energy storage systems due to their high theoretical energy density and safety. However, the practical applications of solid‐state batteries are hindered by severe interfacial issues, such as high interfacial resistance, inferior electro‐/chemical compatibility, as well as poor stability. Moreover, lithium dendrite growth and mechanical degradation caused by interfacial stress during repeated cycling induce the failure of a working solid‐state battery. Therefore, understanding the failure mechanism of a solid‐state lithium battery is imperative and significant to construct a better interface for a safe solid‐state lithium battery. In this review, the current fundamental understanding of the impact of the lithium/solid‐state electrolyte interface on the solid‐state ionics and interfacial chemistry are introduced first. The failure mechanisms underlying electrical, chemical, electrochemical, and mechanical aspects of solid‐state lithium batteries are summarized. The emerging perspectives regarding future research directions are also included. This sheds fresh light on the rational construction of high‐efficiency solid‐state lithium batteries. The failure of solid‐state lithium metal batteries is caused by the electric contact loss and dendrite growth, interphase formation and evolution, and mechanical degradation, which can be mainly associated with the properties of the lithium anode/solid‐state electrolyte (SSEs) interface.